Total quality management and students' attitude as predictors of choice of university of Ibadan distance learning programme (2006)
This work establishes the essence and place of Distance Learning Programme (DPL) in creating more access and opportunities of higher education in the world, particularly in a developing country like Nigeria. It examines the effect of the use of TQM in UIDLP and students' attitude to DLP repectively on the choice of University of Ibadan DLP and their composite effect on students' choice of University of Ibadan Distance Learning Centre. Samples of 100 subjects each from the two sets (200 and 300 levels) of students were selected for the study. Two instruments developed and validated by the researcher were utilized to gather data. The data were analyzed using regression analysis and ANOVA to find how choice was predicted by each and interactively as well as the magnitude of thier respective contribution. The results show that TQM contributes averagly positively to students' choice of programme in 200 level which is higher than what obtained in 300 level (a low positive relationship). The correlation coefficients were 0.460 and 0.056 respectively. At 300 level, students' attitude had a negative relationship with choice of DLP, which was also low but not significant correlation of (r=0.156). Students' attitude correlates with their choice of DL at 200 level at r=0.248 (a low but significant and positive coefficient). However, the joint contribution of TQM and attitude on choice of DLP was a little over average (0.524) at 200 level and low but significant relationship of 0.249 at 300 level respectively. Recommendations based on these were made and these include: making the DL programmes more qualitative through the proper use of the TQM in all its ramifications, giving orientation to both staff and students on the value and use of TQM , in order to engender positive change in students' attitude towards DLP, and adequate funding of the programme for total quality improvement.